Pengaruh Pola Asuh Orang Tua Terhadap Motivasi Belajar Siswa Di SMP Qur’an Sinar Cendekia Boarding School Menurut Perspektif Al-Qur’an - Farhah Nafisatullah Khaerudin; Rahmatul Husni (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
The issue of low learning motivation among students at SMP Quran Sinar Cendekia Boarding School serves as the main background of this study. As an Islamic boarding school, SCBS faces challenges in shaping students’ character and learning motivation, especially due to their diverse parenting backgrounds. Limited interaction between students and parents, along with the lack of synergy in internalizing Qur’anic values such as rahmah (compassion), ta’dib (discipline), and uswah hasanah (exemplary conduct), to contribute to this problem. This study aims to examine the influence of parenting styles on students’ learning motivation from the perspective of the Qur’an. A descriptive quantitative approach was used, with simple linear regression analysis. The sample consisted of 30 students selected using saturated sampling. A questionnaire was used to measure parenting styles (authoritarian, democratic, permissive, neglectful) and student learning motivation based on Uno’s indicators. The results indicate a significant and positive relationship between parenting style and students’ learning motivation. Democratic and Qur’an-based parenting was proven effective in increasing students’ enthusiasm and discipline in learning. These findings highlight the importance of synergy between family and school education in developing a Qur’anic generation with strong character and academic achievement.